2018
DOI: 10.2478/ebtj-2018-0002
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of biotechnology to meeting future food and environmental security needs

Abstract: Biotechnology, including genetic modifications, can play a vital role in helping to meet future food and environmental security needs for our growing population. The nature and use of biotechnology crops are described and related to aspects of food security. Biotechnological applications for food and animal feed are described, together with trends on global adoption of these crops. The benefits of biotechnology crops through increased yield, reduced pesticide use and decreased environmental damage are discusse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 50 publications
0
18
0
1
Order By: Relevance
“…Due to this, new or improved technologies could help feed the world [12]. As the world population growth is doubling, genetic engineering based biotechnological approaches can contribute their incredible roles positively by mitigating the impact of climate change through greenhouse gas (GHGs) reduction, crops adaptation and increase in yield on less land [4]. Previously, convectional biotechnology through tissue culture and convectional breeding as a realistic option that could solve problems of climate change.…”
Section: Beforementioning
confidence: 99%
See 1 more Smart Citation
“…Due to this, new or improved technologies could help feed the world [12]. As the world population growth is doubling, genetic engineering based biotechnological approaches can contribute their incredible roles positively by mitigating the impact of climate change through greenhouse gas (GHGs) reduction, crops adaptation and increase in yield on less land [4]. Previously, convectional biotechnology through tissue culture and convectional breeding as a realistic option that could solve problems of climate change.…”
Section: Beforementioning
confidence: 99%
“…Climate change is one of the most critical challenges currently facing humanity and continue to be a major global problem on sustainable development [1], due to climate change associated factors including unexpected climate change/ temperature rising, can be caused either by the Earth's natural forces such as solar radiation or human activities such as release of GHGs into the atmosphere results in global warming and changes in rain fall amount and patterns [2]. Climate change has a diverse effects on agriculture productivity and quality, rendering food supply less secure in global especially in developing countries [3], while the global population is regularly to increase [4].…”
Section: Introductionmentioning
confidence: 99%
“…Meta-analysis of 147 studies during the past 20 years on Soybean, Maize, Cotton: multitude of benefits revealed that the use of GMO reduced pesticides use by 37%, increased yields by 22%, increased farmer profits by 68% (Klümper and Qaim, 2014).Various review reports showed the role of biotechnology in food security (Abah et al, 2010;Tonukari and Omotor, 2010;Najaf and Lee, 2014;Cano et al, 2017;Gartland and Gartland, 2018) and in sustainable development (Sharad et al, 2010;Adenle, 2015;Björnberg et al, 2015). Similarly, the contribution of GMO in food security has been reviewed by several scholars (Qaim and Kouser, 2013;Lamichhane, 2014;Hallerman and Grabau, 2016;Ouyang et al, 2017;Raman, 2017;Repalli, 2017;Smyth 2017;Gartland and Gartland, 2018;Terefe, 2018). Similarly, the present review is aiming Fig.…”
Section: Contribution Of Biotech Crops To Sustainable Developmentmentioning
confidence: 99%
“…Several developing, agro-based countries like India focus their biotechnology research on food crops and cultivars of high commercial value to meet increasing food requirements and reducing poverty, particularly among resourcepoor farming households. Among multifaceted benefits of plant biotechnology are drought and salt tolerance, and biofortification that enhances micronutrient content, while the relevant modern techniques involve agricultural genome editing, RNA spraying technology and consideration of future targets to strengthen environmental and food security [1]. Indian agriculture currently entails the search, characterization, isolation, and utilization of new genes across taxa for imparting desirable traits in crops through the application of biotechnology.…”
Section: Introductionmentioning
confidence: 99%